Early clinical experience with a degraded 4 MeV electron beam in radiotherapy of superficial basal cell carcinoma - Valve Assi; Koskenmies Sari; Tenhunen Mikko; Nurmi Heidi; Hernberg Micaela; Salminen Samuli; Anttonen Anu (Elsevier, 2026)
The most common non-melanoma skin cancer is basal cell carcinoma (BCC). Surgery is the gold standard treatment but also non-surgical alternatives are needed. The purpose of this work was to present the early clinical experiences of degraded 4 MeV electron beam as a treatment method for superficial BCC. Twelve patients underwent two weeks radiation therapy treatment with either 5 × 7 Gy or 2 × 12 Gy. There were no significant differences in treatment outcome with different fractionations or lesion locations. The degraded beam method is a safe and valid non-surgical solution for suitable patients with superficial lesions.